Annular Beam Shaping in Multiphoton Microscopy to Reduce Out-of-Focus Background. (24th May 2017) - Borglin, Johan; Wang, Danni; Durr, Nicholas J.; Hanstorp, Dag; Ben-Yakar, Adela; Ericson, Marica B.
Abstract : Despite the inherent spatial confinement of multiphoton processes that arises from focusing through an objective, the maximum imaging depth in conventional multiphoton microscopy is ultimately limited by noise from out-of-focus fluorescence. This is particularly evident when imaging beyond shallow depths in highly scattering tissue as increased laser powers are necessary. The out-of-focus signal originates from multiphoton processes taking place primarily at shallow depths and deteriorates contrast and limits imaging depth. In this paper, annular laser beams are explored as a concept to reduce this background signal in multiphoton microscopy. The approach is theoretically verified by data from simulations and proof of principle is demonstrated on a custom-built experimental multiphoton microscopy platform. Annular laser beams were created by adopting wavefront control using a spatial light modulator and implemented for imaging tissue phantoms simulating turbid media and human skin ex vivo. The signal-to-background ratios were calculated and compared to images acquired with a traditional, filled-aperture Gaussian beam. Experiments in tissue phantom show an improvement in signal-to-background ratio of about 30% when using annular beam illumination in comparison to Gaussian illumination at specific depths. When laser power is not the limiting factor, this approach is expected to provide even greater benefits.